Modeling undesirable factors in efficiency evaluation with an application to the Malaysian manufacturing sector / Noor Asiah bt Ramli - Ramli, Noor Asiah (2013)
Efficiency measurement must reflect the realities of production activities. In the manufacturing sector, emissions from fossil fuel combustion, which are acknowledged as being undesirable outputs, should be taken into account in efficiency measurement, since they are produced jointly with desirable outputs. This type of measurement is referred to as eco-efficiency. To analyze eco-efficiency, the Directional Distance Function (DDF) has been a popular approach. However, there is a drawback to the DDF model where the direction vector to the production boundary is fixed arbitrarily, and, hence, may not provide the best efficiency measures. The main purpose of this study is twofold. First, to introduce a new slack-based measure of efficiency called the Directional Slack-based Distance Function (DSDF) model and deploy it to calculate productivity change using the Malmquist Luenberger Productivity Index (MLPI). Second, is to apply the DSDF model to analyze the productivity change in the Malaysian manufacturing sector over the period 2001 to 2010. The regional analysis is conducted on 15 Malaysian states which are categorized into Free Industrial Zone (FIZ) and Non-Free Industrial Zone (N-FIZ) states. Two inputs and two outputs are employed. The inputs are operating expenditure and capital while the desirable and undesirable outputs are sales and carbon dioxide (CO2), respectively. The new DSDF model determines the optimal direction to the frontier for each unit of analysis and provides dissimilar expansion and contraction factors to achieve a more reasonable eco-efficiency score. The DSDF is more appropriate than the DDF because the desirable and undesirable outputs can be expanded and contracted, respectively, in different proportions. In addition, two stage analyses with a three-year ‘window’ of data is employed to overcome the infeasibility problem that may occur in the MLPI calculated by DDF. The application of the DSDF demonstrates that the eco-efficiency scores for the states under the N-FIZ category are higher than the states under the FIZ category reversing the results of the DDF model. Johor and Selangor, which have many heavy industries releasing higher levels of air pollution, appeared to have the poorest eco-efficiency scores using the DSDF model. Considering the scale direction for undesirable output is larger than the desirable output, it shows that Malaysian states need to prioritize the reduction of CO2 in manufacturing activities followed by an increment in sales. As for the productivity change, it was found that the main source of the productivity deterioration when taking CO2 emissions into account is eco-efficiency change. This study offers methodological contribution by introducing the DSDF model to overcome the drawback of the DDF model and solving the infeasibility problem that may occur in MLPI when using the DDF model. In terms of empirical contribution, it presents a comprehensive model that integrates the indicators between the environmental and industrial elements to measure the eco-efficiency in the Malaysian manufacturing sector. The findings also provide important policy implications. Among others, the study suggests the introduction of a carbon tax policy for organizations so that the manufacturing sector is more environmentally responsible while focusing on production sustainability.